2015
DOI: 10.1111/bph.13065
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants of positive allosteric modulation of the human metabotropic glutamate receptor 2

Abstract: BACKGROUND AND PURPOSEThe activation of the metabotropic glutamate receptor 2 (mGlu2) reduces glutamatergic transmission in brain regions where excess excitatory signalling is implicated in disorders such as anxiety and schizophrenia. Positive allosteric modulators (PAMs) can provide a fine-tuned potentiation of these receptors' function and are being investigated as a novel therapeutic approach. An extensive set of mutant human mGlu2 receptors were used to investigate the molecular determinants that are impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 46 publications
8
53
1
Order By: Relevance
“…As a general trend in this pyrazole series the in vitro activity for the mGlu 2 receptor increases with lipophilicity (as exemplified by introduction of the chlorine substituent in compounds 18 – 19 ). This is not unusual, as the allosteric binding site is believed to be in the 7‐transmembrane (7TM) region . Nevertheless, this higher lipophilicity results in lower unbound brain fraction.…”
Section: Initial Mglu2 Nam Gtpγs Sar Study Of the Anilinementioning
confidence: 98%
See 2 more Smart Citations
“…As a general trend in this pyrazole series the in vitro activity for the mGlu 2 receptor increases with lipophilicity (as exemplified by introduction of the chlorine substituent in compounds 18 – 19 ). This is not unusual, as the allosteric binding site is believed to be in the 7‐transmembrane (7TM) region . Nevertheless, this higher lipophilicity results in lower unbound brain fraction.…”
Section: Initial Mglu2 Nam Gtpγs Sar Study Of the Anilinementioning
confidence: 98%
“…To prove mGlu 2 target engagement, an ex vivo occupancy assay in rat native tissue was set up . Site‐directed mutagenesis studies have shown that mGlu 2 NAMs and PAMs share multiple amino acid residues in their allosteric binding pocket which influence their activity, therefore suggesting a common binding site. Based on this, the tritiated selective mGlu 2 positive allosteric modulator (PAM) ligand [ 3 H]JNJ‐46281222 previously developed by our team, was used to conduct the ex vivo occupancy studies .…”
Section: Initial Mglu2 Nam Gtpγs Sar Study Of the Anilinementioning
confidence: 99%
See 1 more Smart Citation
“…In silico and modeling approaches such as docking and molecular dynamics (MD) simulation have been utilized for probing ligand fit and calculating time-dependent GPCR conformational changes in the millisecond to femtosecond range following allosteric ligand engagement, in some cases adjunctive to crystallographic analyses [14,28,99,105108]. Experimental techniques such as nuclear magnetic resonance spectroscopy (NMR) [109,110], site-directed mutagenesis coupled with quantitative pharmacological analyses [111114] or long-timescale MD simulations [115] have also been applied to gain structural insight into GPCR allostery. Such approaches have also helped define structure–activity relationships among GPCR-targeted allosteric scaffolds [116,117].…”
Section: Localization and Architecture Of Cb1r Allosteric Ligand-bmentioning
confidence: 99%
“…Early mutagenesis studies identified three amino acid residues in transmembrane (TM) segments IV and V of mGlu 2 R to be critical for the activity of LY487379 and several other mGlu 2 R PAMs [111, 112]. A more recent extensive study identified additional residues in TM III, V, and VI to play an important role in the activity of mGlu 2 R PAMs [113]. Interestingly, 3 residues in TM IV of mGlu 2 R have been found to be essential for the heteromerization of 5-HT 2A -mGlu 2 R [68] indicating that TMD region of mGlu 2 R is implicated in different types of allosteric interactions.…”
Section: Promise Of Mglur Positive Allosteric Modulatorsmentioning
confidence: 99%